Perancangan Sistem Informasi Kesiswaan di MI Terpadu X - Abdul Muksith; Otong Rukmana (Jurnal Riset Teknik Industri, 2022)
Abstract. MI Terpadu X is an elementary school that has several administrative processes, one of which is student administration. The activities in the student administration are considered less effective because there is no regular relationship between aspects of student administration activities plus the Covid-19 pandemic condition which makes it difficult for school workers, teachers as well as parents and students to access data quickly plus the number of students who continue to work. increasing every year so that there is a need to improve the quality of national education standards in the management aspect with the aim of building good administrative services. An alternative in solving problems experienced by student administration is to design an information system for student administration services using the Prototyping information system development method. The Prototyping method is a method that builds a prototype design to make it the basis before making the actual system. This method has four main stages, namely planning, analysis, design and implementation by communicating openly to the school workforce to create the system they want. Based on data processing, it is obtained that the student administration information system design has been arranged in a system by maximizing the function of the administrative section as the manager to store data related to student administration used by the student department, treasurer, homeroom teacher, curriculum and other sections so that storage data becomes centralized and can be accessed by parents, prospective students and students through the website presented. Abstrak. MI Terpadu X merupakan sekolah tingkat dasar yang memiliki beberapa proses administrasi salah satunya adalah administrasi kesiswaan. Kegiatan yang ada di administrasi kesiswaan tersebut dinilai kurang efektif karena tidak adanya hubungan yang teratur antar aspek kegiatan administrasi kesiswaan ditambah kondisi pandemi Covid-19 yang menyulitkan tenaga kerja sekolah, guru maupun orang tua dan siswa dalam mengakses suatu data secara cepat ditambah jumlah siswa yang terus meningkat setiap tahunnya sehingga perlu adanya peningkatan kualitas standar nasional pendidikan pada aspek pengelolaan dengan tujuan untuk membangun layanan administrasi yang baik. Alternatif dalam penyelesaian masalah yang dialami oleh administrasi kesiswaan adalah merancangan sistem informasi layanan administrasi kesiswaan dengan menggunakan metode pengembangan sistem informasi Prototyping. Metode Prototyping merupakan metode yang membangun rancangan prototype untuk menjadikannya landasan sebelum membuat sistem sesungguhnya. Metode ini memiliki empat tahapan utama yaitu perencanaan (planning), analisis (analysis), perancangan (design) dan implementasi (implementation) dengan mengkomunikasikannya secara terbuka kepada tenaga kerja sekolah untuk membuat sistem yang mereka inginkan. Berdasarkan pengolahan data diperoleh rancangan sistem informasi administrasi kesiswaan telah diatur secara sistem dengan memaksimalkan fungsi dari bagian tata usaha sebagai pengelolanya untuk menyimpan data data yang berkaitan dengan administrasi kesiswaan yang digunakan oleh bagian kesiswaan, bendahara, wali kelas, guru, kurikulum dan bagian lainnya sehingga penyimpanan data menjadi terpusat serta dapat diakses oleh orang tua, calon siswa dan siswa melalui website yang disajikan.